2020
DOI: 10.3390/v12060628
|View full text |Cite
|
Sign up to set email alerts
|

Broad-Spectrum Host-Based Antivirals Targeting the Interferon and Lipogenesis Pathways as Potential Treatment Options for the Pandemic Coronavirus Disease 2019 (COVID-19)

Abstract: The ongoing Coronavirus Disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) signals an urgent need for an expansion in treatment options. In this study, we investigated the anti-SARS-CoV-2 activities of 22 antiviral agents with known broad-spectrum antiviral activities against coronaviruses and/or other viruses. They were first evaluated in our primary screening in VeroE6 cells and then the most potent anti-SARS-CoV-2 antiviral agents were further evaluated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 71 publications
2
47
2
Order By: Relevance
“…Among IFNs, the most reductive effects on viral load belonged to IFN β-1a and IFN β-1b. However, IFN β-1b showed highest potency and selectivity index against SARS-COV-2 [22] .…”
Section: Discussionmentioning
confidence: 94%
“…Among IFNs, the most reductive effects on viral load belonged to IFN β-1a and IFN β-1b. However, IFN β-1b showed highest potency and selectivity index against SARS-COV-2 [22] .…”
Section: Discussionmentioning
confidence: 94%
“…Apilimod, a PIKFYVE inhibitor and promising therapeutic in multiple SARS-CoV-2 models (Kang et al, 2020;Riva et al, 2020) including heterokaryon assays tested herein ( Figures 3E; S3B), prevented pseudoparticle entry at nanomolar concentrations ( Figure 7B). By contrast, 25-hydroxycholesterol, which lowers plasma membrane cholesterol by redirection to the cell interior (Abrams et al, 2020;Im et al, 2005;Wang et al, 2020;Yuan et al, 2020;Zhu et al, 2020b;Zu et al, 2020), had no effect ( Figure 7C). However, MBCD, which directly "strips" plasma membrane cholesterol without engaging intracellular targets (Zidovetzki and Levitan, 2007), blocked virus entry ( Figure 7D).…”
Section: Sars2-cov-2 Infection Depends On Membrane Cholesterol Of Thementioning
confidence: 88%
“…These interferons have been found to have positive therapeutic effects in the treatment of viral infections including hepatitis [14], and coronaviruses such as SARS and MERS [15,16]. One investigation assessed Type I recombinant interferon to be one of the most potent anti-SARS-CoV-2 antiviral agents [17]. Additionally, a recent investigation revealed that several severe cases of COVID-19 presented with a rare, X-chromosome lossof-function mutation that impaired Type I interferon response [18], while another demonstrated an association between COVID-19 severity and Type I interferon deficiency [19].…”
Section: Introductionmentioning
confidence: 99%